"I was worried if I don't have a broken leg they might not take it seriously": Experiences of men accessing ambulance services for mental health and/or alcohol and other drug problems. (4th April 2019) - Ferguson, Nyssa; Savic, Michael; McCann, Terence V.; Emond, Kate; Sandral, Emma; Smith, Karen; Roberts, Louise; Bosley, Emma; Lubman, Dan I.
Abstract: Background: A large proportion of ambulance callouts are for men with mental health and/or alcohol and other drug (AOD) problems, but little is known about their experiences of care. This study aimed to describe men's experiences of ambulance care for mental health and/or AOD problems, and factors that influence their care. Methods: Interviews were undertaken with 30 men who used an ambulance service for mental health and/or AOD problems in Australia. Interviews were analysed using the Framework approach to thematic analysis. Results: Three interconnected themes were abstracted from the data: (a) professionalism and compassion, (b) communication and (c) handover to emergency department staff. Positive experiences often involved paramedics communicating effectively and conveying compassion throughout the episode of care. Conversely, negative experiences often involved a perceived lack of professionalism, and poor communication, especially at handover to emergency department staff. Conclusion: Increased training and organizational measures may be needed to enhance paramedics' communication when providing care to men with mental health and/or AOD problems.